Studi Literature Review: Kajian Filologi terhadap Naskah Kuno Hadis di Indonesia - Ahmad Fauzi; Edriagus Saputra; Siti Suaibah; Ahmad Sapani; Ahmad Sahril; Siti Wardah; Arwansyah bin Kirin (Al-Mu'tabar, 2026)
Ancient hadith manuscripts as an Islamic intellectual heritage in Indonesia reflect the dynamics of hadith transmission and adaptation in local contexts, but the increase in philological publications has not been accompanied by a comprehensive mapping of trends, methods, and scholarly contributions. This article answers the main question: how are publication trends, methodological approaches, and contributions to philological research on ancient hadith manuscripts in Indonesia developing, and what research gaps need to be addressed? The novelty of this research lies in a systematic literature review that integrates bibliometric analysis to uncover gaps such as the dominance of descriptive approaches and the lack of integration with classical hadith science. The methodology uses a qualitative literature review, a search of 30 articles via Google Scholar with the keyword "ancient manuscripts", data analysis using Dimensions AI, and classification in tables, graphs, and narratives to map journal affiliations, regions, and accreditation. The main results show an increasing publication trend since 2018 (peaking at 5 articles in 2019 and 2022), a dominance of Padjadjaran University and UIN Raden Fatah Palembang, a concentration in Java and Sumatra, and the majority of publications in non-SINTA journals. The discussion underlines the integration of philology-hadith as a complementary approach to textual criticism, sanad, matan, and heritage preservation, encouraging more integrative and contextual research.